Database Services for Cloud Computing – An Overview - Malliga, P. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cloud computing has revolutionized the way computinginfrastructure is abstracted and used. There is a proliferation ofnumber of applications which leverage various cloud platforms,resulting in a tremendous increase in the scale of data generated aswell as consumed by such applications. This paper reviews thefeatures of Cloud computing and then gives a survey of differentdatabase architecture for cloud computing. Scalable databasemanagement systems are a crucial part of the cloud infrastructurewhich includes both update intensive workloads and decisionsupport systems. The paper presents an organized picture of thechallenges and open issues pertaining to database managementsystems in developing and deploying internet scale applications inthe cloud environment. The typical properties of commerciallyavailable databases for cloud computing environment are alsobrought out.